Laporan Keuangan Masjid Berdasarkan Kombinasi PSAK Nomor 45 dan PSAK Nomor 109 (Studi Kasus Pada Masjid XYZ) - Dewi Yibta Nariasih; Taufik Kurrohman; Andriana Andriana (UPT Penerbitan Universitas Jember, 2017)
This research aims to know the financial statements have been drawn up by the institutions of the mosque especially XYZmosque for later comparison with the PSAK Number 45 and PSAK Number 109 and solved into the financial statements basedon the combination of PSAK Number 45 and PSAK Number 109. The Type of this research is a qualitative descriptive by usingprimary and secondary data collected by using the techniques of observation, interviews, and documentation. In this researchthe author did data analysis by collecting, reduction, and serves data to be drawn a conclusion. The validity of data waschecked using the triangulation method. The results of this research are the financial statements have been prepared by XYZmosque are still not in accordance with the PSAK Number 45 and or PSAK Number 109. Financial report compiled by XYZmosque still in the form of a simple cash book. The combination is done by compiling financial position reports and activityreports based on PSAK Number 45 in which account assets neto was changed to fund balance, asset-run changes report basedon PSAK Number 109, and the cash flow statement and the notes of financial statements based on PSAK Number 45.